2014
DOI: 10.1155/2014/493495
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Recovery in Response to the Exclusion of Grazing by Sika Deer (Cervus nippon) in Seminatural Grassland on Mt. Kushigata, Japan

Abstract: We examined the recovery of vegetation in seminatural grassland in central Japan after eliminating grazing by sika deer (Cervus nippon) by fencing. By 2012, after 5 years of fencing for exclusion of sika deer, the species composition of quadrats within the enclosure reverted to the original species composition in 1981, not browsed by sika deer. Conversely, outside the fence was different from the baseline quadrats in 1981. Iris sanguinea, a prominent flower in the area, recovered within the enclosure, while it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Readers are referred to some more specifics of the discussion for the restoration of firs and other tree species carried out at many forests of the world (Hester et al 2000, Kay and Bartos 2000, Halpern 2001, Takahashi et al 2001, Narukawa and Yamamoto 2002, Ito and Hino 2004, Taylor et al 2004, Dobrowolska 2008, Doležal et al 2009, Pellerin et al 2010, Nagaike et al 2014, Bottero et al 2015. It is worth to pay due attention to measure appropriate vegetation indices on forest ecosystems impacted by deer (Iijima and Nagaike 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers are referred to some more specifics of the discussion for the restoration of firs and other tree species carried out at many forests of the world (Hester et al 2000, Kay and Bartos 2000, Halpern 2001, Takahashi et al 2001, Narukawa and Yamamoto 2002, Ito and Hino 2004, Taylor et al 2004, Dobrowolska 2008, Doležal et al 2009, Pellerin et al 2010, Nagaike et al 2014, Bottero et al 2015. It is worth to pay due attention to measure appropriate vegetation indices on forest ecosystems impacted by deer (Iijima and Nagaike 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported the disturbance of regeneration of tree species by ungulate browsing around the world (Wilson 1969, Gill 1992, Waller and Alverson 1997, Potvin et al 2003, Rooney and Waller 2003, Senn and Suter 2003, Weisberg and Bugmann 2003, Cote et al 2004, Tsujino and Yumoto 2004, Pepin et al 2006, Takatsuki 2009, Hidding et al 2012, Nagaike et al 2014Cutini et al 2015, Swiss Federal Institute for Forest 2015; a few studies were carried out on the dynamics and the other ecological issues of roe deer in Korea (Kim and Kim 2001, Kim 2006, Kim and Hong 2006, Kim et al 2007a, Jeon and Kim 2011, Jo et al 2012, 2013, Kang 2013. In addition, studies on the dynamics of forest stands indicated that competition with other species of understory vegetation such as dwarf bamboo (genus Sasa) can interrupt the establishment of the seedlings of the natural tree species at forest stands of the world (Nakashizuka 1988, Peters et al 1992, Abe et al 2001, Taylor et al 2004, 2006, Doležal et al 2009, Song et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted our study in Yamanashi Prefecture, central Japan. In Japan, Deer (Cervus nippon) have been expanding their distribution since the late 1980s (Takatsuki, 2009), and debarking and browsing have recently become serious problems (Takatsuki, 1989;Akashi and Nakashizuka, 1999;Ando et al, 2004), a trend that has also been observed in Yamanashi Prefecture (Nagaike and Hayashi, 2003;Jiang et al, 2005;Nagaike 2012;Nagaike et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to elevation, the amount of attractive habitat (e.g., subalpine grassland) may affect deer density. Deer generally prefer herbaceous plants to woody plants (Takatsuki 1986;Winnie 2012), and severe browsing of herbaceous plants in subalpine grasslands by deer has been reported (Schütz et al 2003;Nagaike 2012;Nagaike et al 2014). Thus, subalpine forests which were surrounded by large subalpine grasslands would be more susceptible for debarking by deer.…”
Section: Introductionmentioning
confidence: 99%